Morphology and Morphometry of Thyroid Gland in Cadavers: A Descriptive Cross-Sectional Study - Phuyal, Navindra; Shrestha, Anusuya; Bhandari, Rosha; Adhikari, Bidur; Gautam, Jyoti; Dhungel, Deepesh; Gautam, Subina; Ranjit, Nirju (Journal of Institute of Medicine Nepal, 2024)
Introduction Variations in anatomy of thyroid gland include the occasional presence of a pyramidal lobe and a fibromuscular band called levator glandulae thyroideae. These variations affect the gland's morphometry and morphology. This study aimed to study morphometry and variation prevalence of thyroid gland. Methods This descriptive study examined adult cadavers from the Department of Forensic Medicine at Maharajgunj Medical Campus. Measurements of the length, breadth, and thickness of both lateral lobes and the isthmus were taken. The presence or absence of the isthmus, pyramidal lobe, and levator glandulae thyroideae was recorded, along with the origin and dimensions of the pyramidal lobe, if present. Results The mean dimensions of the right lobe were 43.88±6.88 mm (length), 23.93±4.76 mm (breadth), and 12.28±3.30 mm (thickness). For the left lobe, the measures were 40.47±7.26 mm, 21.95±4.22 mm, and 12.84±3.61 mm, respectively. The isthmus had mean dimensions of 18.12±5.52 mm, 16.65±5.51 mm, and 5.10±1.76 mm. The isthmus was absent in 7.2% of cases. The pyramidal lobe, present in 27.8% of cases, had mean dimensions of 19.17±8.26 mm, 11.64±3.47 mm, and 4.60±1.33 mm, typically originating from the center of the isthmus. The average weight of the thyroid gland was 16.19±5.22 g. Conclusion The thyroid gland's weight was higher in males and positively correlated with the individual's height. Also, thyroid gland's dimensions and weight were less than those described in standard texts. The relationship between body weight and thyroid gland weight warrants further investigation.